Aerobiological Monitoring in an Indoor Occupational Setting Using a Real-Time Bioaerosol Sampler - Andrea Lancia; Angela Gioffrè; Federico Di Rita; Donatella Magri; Maria Concetta D’Ovidio (Atmosphere, 2023)
Aerobiological monitoring is a crucial tool for human and environmental health. Real-time bioaerosol samplers are major innovative techniques for aerobiological monitoring. In this study, we evaluate the use of a real-time bioaerosol sampler to monitor the exposure in an indoor occupational environment. We used a WIBS-NEO sampler, continuously operating during working and non-working days. The fluorescent particles were 16.5% of the total, identifiable as bioparticles. There was a significant difference between working and non-working days regarding bioparticles (+19% on average), especially in the morning (+91% on average), the part of the day mostly associated to worker presence. In working days, there is a difference between working and non-working-hours, reinforced by a strong correlation between the time of occupation of the room and the number of particles identified as pollen and fungal spores (R2 = 0.741, p < 0.01). The bacterial component does not seem to be influenced by the presence of workers; however, it follows the general distribution of bioparticles. Our results indicate the reliability of the real-time instrument for the monitoring of different biocomponents, and the role of workers in the distribution of some types of bioaerosol particles, like pollen and fungal spores, which can have several health impacts, such as allergies.